Chapter Sl.eccl. pазумъ. Studi per un lexicon plurilingue dei termini religiosi e filosofico-teologici - Ferro, Maria Chiara (Biblioteca di Studi Slavistici, 2018)
The paper aims at defining the meaning of Church Slavonic разумъ in medieval and pre-modern Eastern Slavic sources, on the basis of the historical section of Russian National Corpus. Compared with the entries of Old Slavonic and Church Slavonic dictionaries, the query results allow a more exact understanding of the semantics of the word and of its contexts of use, which is useful in the determination of Italian equivalents and relevant in compiling a multilingual lexicon of religious and philosophical-theological words.